(untitled) (Gestão & Regionalidade, 2017)
This research aimed to investigate the relationship between how an organization monitors its external environment and its strategic orientation and it was based on the theoretical model of Daft and Weick. These two constructs were assessed through the perception of professionals related to monitoring activities in the organizations they serve. The approach chosen was quantitative, using the survey as research method. Data were analyzed by using descriptive statistics, non-parametric and multivariate analysis. The results indicate a relationship between the two constructs investigated, and the formal search for information stood out more in the analytical and prospector organizations and informal search, in the reactive and defensive.